Direct antiviral drugs and blocking monoclonal antibodies as the basis of etiotropic therapy of a novel coronavirus infection - V. B. Musatov (Журнал инфектологии)
At the beginning of 2020, a pandemic of a novel coronavirus infection was declared in the world. Since the beginning of the pandemic, the search for drugs for etiotropic therapy as the basis for the treatment of the infectious process has begun. The review provides data on the application points of antiviral activity of drugs, taking into account the life cycle of the etiological agent – the SARS-CoV-2 virus. The mechanisms of drug action on RNA-dependent RNA polymerase (molnupiravir, remdesivir, favipiravir) and protease (nirmatrelvir together with ritonavir) SARS-CoV-2 are described. Among of outpatient patients at risk, the use of molnupiravir up to 5 days from the onset of the disease provided a 30% reduction in the risk of hospitalization and an 89% reduction in the risk of death. The use of a 10-day course of remdesivir in inpatient patients led to a reduction in the duration of clinical manifestations by 5 days, and the use of the drug for 3 days on an outpatient basis had a beneficial effect on a group of high-risk patients in the form of a reduction in the risk of hospitalization and death by 87%. Among outpatient patients using favipiravir, the onset of clinical improvement was noted 4 days earlier compared to the control group. The administration of nirmatrelvir in combination with ritonavir on an outpatient basis led to an 89% reduction in the risk of hospitalization or death. The molecular basis and principles of the use of blocking monoclonal antibodies as a fundamentally new group of biological drugs for etiotropic therapy are discussed. Information is provided on the effects of drugs on alpha, beta, gamma, delta and omicron variants of the virus. The profile of drug-drug interaction of drugs and basic therapy is analyzed. Early initiation of etiotropic therapy on an outpatient regime provides a more favorable course of the disease, which is characterized by a shorter duration of clinical manifestations, a reduced risk of hospitalization and the onset of death.